Detecting coastal ocean mass variations with GRACE mascons. Issue 3 (14th March 2019) - Mu, Dapeng; Xu, Tianhe; Xu, Guochang
SUMMARY: Knowledge of the coastal ocean mass variations is important for understanding the ocean climate and sea level change. However, estimates of coastal ocean mass variations have been perplexed due to poor representativeness of previous Gravity Recovery and Climate Experiment (GRACE) data across the land/ocean boundary. We here use GRACE mascon solutions to investigate the coastal ocean mass variations (within 400 km band) at global and regional scales. GRACE mascon solutions are advanced by spatial constraints and leakage correction. For the global mean, it is found that mascons ocean mass variations are in rough agreement with those inferred from satellite altimeter and an ocean analysis; the agreement is better on seasonal scales (6.4 ± 0.5 mm annual amplitude for the mascons and 7.3 ± 0.7 mm annual amplitude for the inferred); on the other hand, large differences are shown for the linear trend (2.1 ± 0.1 mm yr −1 for the mascons and 3.2 ± 0.1 mm yr −1 for the inferred), indicating that it is far from closing the coastal sea level budget. At regional scales, high consistency between mascons and the inferred is observed over two shallow areas, that is, Europe coast and East China coast, whose annual amplitudes are 24 ± 5 and 42 ± 3 mm, respectively. Ocean mass variations are not well captured by mascons over other regions (e.g. Africa coast, Indian coast and North and South America coast). Possible explanations include (1) the steric component plays a more important role in sea level, consequently resulting in weak mass signal and (2) the performance of mascons varies with locations. We find that mascon solutions show better variability (especially seasonal cycles) than do the traditional spherical harmonic coefficients, suggesting that mascons applied with spatial constraints improve the coastal ocean mass variability.